Dreaming in the Digital Age: Thoughts on the Technological Pharmakon - Krebs, Victor J. (Poligrafi, 2023)
This article explores one way of understanding how digital media are affecting our ability to distinguish reality from fantasy, by reading Bernard Stiegler’s diagnosis of our current cultural crisis, alongside Wilfred Bion’s dream theory. The central claim of the paper is that we can understand the technological pharmakon, its both poisonous and therapeutic nature, in terms of Bion’s definition of dreaming, as the commerce between consciousness and the unconscious negotiated by the “alpha function”. Understanding how the digital impacts our capacity to dream provides us with a tool to counteract its toxicity and to combat the thanatic impulse triggered by technological power. From a binocular point of view – both from Stiegler’s perspective of our technical or “organological” evolution and from Bion’s perspective on the constitution of reality in dreaming – we can begin to see more clearly how to modulate our technological drive, in order to prevent the pharmakon from short-circuiting the very psychic function necessary to distinguish between reality and illusion. The paper ends with a discussion of the algorithmic effects on the living imagination in support of this contention.